2014
DOI: 10.1007/s40145-014-0125-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of MgF2 addition on high energy ball milled kalsilite: Implementation as dental porcelain with low temperature frit

Abstract: Porcelain fused to metal (PFM) has received great attention over the last few years due to its importance in the dentistry. Kalsilite (K 2 O·Al 2 O 3 ·SiO 2 ) is a high thermal expansion porcelain, suitable for bonding to metals. However, kalsilite is a metastable phase which gets converted into crystalline leucite upon heating. In the current work feasibility of developing stable kalsilite phase, dispersion of MgF 2 in it as an additive and using mechanochemical synthesis are studied. Micro fine dental materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The molten frit was quenched in deionized water, dried at 110 1C for 2 h and subsequently pulverized to pass a 350 BSS mesh. A similar process was adopted for the preparation of LTF details, which is described elsewhere [17].…”
Section: Preparation Of Leucite Bioglass and Ltfmentioning
confidence: 99%
See 1 more Smart Citation
“…The molten frit was quenched in deionized water, dried at 110 1C for 2 h and subsequently pulverized to pass a 350 BSS mesh. A similar process was adopted for the preparation of LTF details, which is described elsewhere [17].…”
Section: Preparation Of Leucite Bioglass and Ltfmentioning
confidence: 99%
“…This work also reports preparation of bioglass and low temperature frit (LTF) by traditional melt-quenching method [17,18]. Above three materials were mixed in an optimum ratio to form a composite with desirable properties.…”
Section: Introductionmentioning
confidence: 99%
“…One way of reducing the sintering temperature of porcelain is to add a sintering additive to the raw materials. Several sources of research have reported that the sintering temperature decreased by mixing metal oxides or other fluxing agents into porcelain, whereas these expensive sintering aids are hardly applied to porcelain production [ 10 , 11 , 12 , 13 , 14 ]. O. Turkmen reduced the firing temperature of 25 °C of hard porcelain by 1 wt% wollastonite addition, but the bending strength decreased and the porosity increased [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…KAlSiO 4 is a feldspathoid with a structure of (Si, Al)O 4 tetrahedral framework . Kalsilite is a basic silicate mineral which can be used for PFM due to its high CTE and high flexural strength . Becerro et al .…”
Section: Introductionmentioning
confidence: 99%
“…For the last few years, synthesis of kalsilite has become an attractive subject, especially for veneering applications. Synthesis of kalsilite has been studied using various methods such as mechanochemical, solid‐state, and hydrothermal processes …”
Section: Introductionmentioning
confidence: 99%